Tratamento do deslocamento de disco com redução em pacientes diagnosticados pelo RDC/TMD: uma revisão sistemática da literatura - Rolim, Larissa Santos Amaral (2014)
Temporomandibular Disorders (TMD) corresponds to problems related to the temporomandibular joint (TMJ) and to disorders associated to structures of the masticatory apparatus, such as the muscles and teeth.The aim of this study was analyze, through a systematic review of literature of randomized clinical trials, the types of treatments for the displacement of the articular disc of the TMJ with reduction diagnosed by the criteria of the RDC / TMD index.The aim of this review was to analyze the different types of treatment for disc displacement with reduction and effectiveness in the treatment of TMD. The following terminology was searched in PubMed/MEDLINE database: “TMJ disc displacement with reduction AND treatment”, “TMJ disc displacement with reduction AND management”, “Disc displacement with reduction AND treatment”, “Disc displacement with reduction AND management”, “TMJ Disc dislocation with reduction AND treatment”, “TMJ Disc dislocation with reduction AND management”, “TMJ clicking AND treatment”, “TMJ clicking AND management”. From a total of 44 articles selected for full reading, only 4 articles were in conform to all the inclusion criteria. In all studies, the highest prevalence in seeking treatment for TMD were women. 46.15% of the articles did not use or do not fully informed the RRC as a diagnostic criterion, being responsible for most of the exclusion of articles. It was not possible to make a comparison regarding the effectiveness of treatments for TMD, since the methodology, the type of treatment, techniques and the achievement of the results were different. All studies were able to demonstrate, through the Visual Analogue Scale (VAS), the efficiency of each treatment with the recession of the painful symptoms. Most functions assessed in the studies showed significant improvement after the treatment. Only one article assessed the presence of joint clicking and its improvement after treatment. Thus, there should be a standardization of diagnostic methods for a better comparison between the results and further studies should be conducted to assess the joint clicks.